Stress analysis of circular disk using shear difference method in reflection polariscope - Yongyut Manjit (2019)
© All right Reserved 2019 The induced stress relation of PMMA (Poly methyl methacrylate) was investigated by two-point loading of hydraulic press system at top and bottom of circular disk shape and we observed the angle of principal stress and number of fringe order of isoclinic and isochromatic fringe pattern using reflection polariscope. It was found that the number of fringe order depended on magnitude of force but the angle of principal stress did not depend on the magnitude of force. The fringe value of circular disk calculated by calibration method was 57,920 N/(order fringe) and these parameters were used to calculate stress distribution by shear difference method. The results show the stress distribution of circular disk and the relation of stress distribution with the magnitude of force consist of shear and normal stress. The stress of circular disk increased as the magnitude of force increased. The relation of the force (in the magnitude of 535.4-994.6 N) with shear stress, normal stress in horizontal and vertical direction of circular disk is linear.